Rapid and Sensitive Detection of Salmonella spp. Using CRISPR-Cas13a Combined With Recombinase Polymerase Amplification - An, Bailin; Zhang, Hongbin; Su, Xuan; Guo, Yue; Wu, Tao; Ge, Yiyue; Zhu, Fengcai; Cui, Lunbiao (Frontiers in Microbiology, 2021)
Salmonella spp. is one of the most common foodborne disease-causing pathogens that can cause severe diseases in very low infectious doses. Rapid and sensitive detecting Salmonella spp. is advantageous to the control of its spread. In this study, a conserved short fragment of the Salmonella invA gene was selected and used to design primers and specific crRNA (CRISPR RNA) for establishing a one-tube and two-step reaction system for Salmonella spp. detection, by combining recombinase polymerase amplification (RPA) with CRISPR-Cas13a (Clustered Regularly Interspaced Short Palindromic Repeats associated protein 13a) cleavage. The established one-tube RPA-Cas13a method can complete the detection within 20 minutes and the two-step RPA-Cas13a method detection time within 45 minutes. The designed primer set was highly specific to Salmonella spp. and had no cross-reaction with the other nine diarrheal bacteria. The one-tube RPA-Cas13a could detect the Salmonella genome with the limit of 102 copies which was the same as real-time PCR, but less sensitive than two-step RPA-Cas13a (100 copies). The detection results of one-tube or two-step RPA-Cas13a and real-time PCR were highly consistent in clinical samples. One-tube RPA-Cas13a developed in this study provides a simple, rapid, and specific detection method for Salmonella spp. While two-step assay was more sensitive and suitable for samples at low abundance.